HBsAg, anti-HCV, anti-HIV 1/2 and syphilis seroprevalence in healthy volunteer blood donors in southeastern Anatolia - Dayan, Saim; Tekin, Alicem; Tekin, Recep; Dal, Tuba; Hoşoğlu, Salih; Yazgan, Umit Can; Bekçibaşı, Muhammet; Gül, Kadri (The Journal of Infection in Developing Countries, 2013)
Introduction: This study investigated the seroprevalence of hepatitis B virus surface antigen (HBsAg), antibody against hepatitis C virus (anti-HCV), antibody against human immunodeficiency virus type 1/2 (anti-HIV 1/2), and antibody against Treponema pallidum (anti-Treponemal or syphilis antibody) in healthy volunteer blood donors, and assessed their distribution according to the years and genders. Methodology: HBsAg, anti-HCV, anti-HIV ½, and syphilis screening results of a total of 266,035 healthy volunteer blood donors who had been admitted for blood donation to the Regional Blood Center of Dicle University Hospital between January 2000 and December 2010 were evaluated, retrospectively. HBsAg, anti-HCV, and anti-HIV 1/2 screening were performed using a fully automated device with the microparticle enzyme immunoassay method (MEIA). Syphilis screening was performed by Rapid Plasma Reagin (RPR) carbon test between January 2000 and December 2009, and by using a fully automated device with the MEIA method between January 2010 and December 2010. Results: Of 266,035 healthy volunteer blood donors, 259,384 (97.5%) were male and 6,651 (2.5%) were female. Statistically, there was not any significant difference between male and female genders for HBsAg, anti-HCV and syphilis seropositivities (P = 0.729, P = 0.748, and P = 0.861, respectively). HBsAg was found to be positive in 8,422 (3.17%), anti-HCV in 1,703 (0.64%), anti-HIV 1/2 in one (0.0004%) of 266,035 healthy volunteer blood donors, and syphilis antibody with RPR in 166 (0.07%) of 246,341 healthy volunteer blood donors. Conclusion: Blood donor forms should be carefully tailored to improve the identification of possible risks of transfusion-transmitted infections.